Effects of fungal seed endophyte FXZ2 on Dysphania ambrosioides Zn/Cd tolerance and accumulation - Sharma, Vijay K.; Parmar, Shobhika; Tang, Wenting; Hu, Haiyan; White, James F.; Li, Haiyan (Frontiers in Microbiology, 2022)
Metal induced oxidative stress in the contaminated soils affects the plant growth. In the present study, we evaluated the role of seed endophyte FXZ2 on Dysphania ambrosioides Zn/Cd tolerance and accumulation. A series of pot experiments were conducted under variable Zn (500, 1000, 1500 mg kg-1) and Cd (5, 15, 30, 60 mg kg-1). The results demonstrated that FXZ2-inoculation significantly enhanced the growth of D. ambrosioides, improved its chlorophyll and GSH content. In the rhizosphere, FXZ2 inoculation changed the chemical speciation of Zn/Cd and thus affected their uptake and accumulation in host plants. The exchangeable and carbonate-bound fractions (F1+F2) of Zn decreased in the rhizosphere of FXZ2-inoculated plants (E+) as compared to non-inoculated plants (E-) under Zn stress (500 and 1000 mg kg-1), correspondingly, Zn in the shoots of E+ decreased (p<0.05). However, at Cd stress (30 and 60 mg kg-1), the F1+F2 fractions of Cd in E+ rhizospheric soils increased, subsequently, Cd in the shoots of E+ increased (p<0.05). FXZ2 could exogenously secrete phytohormones IAA, GA, and JA. The study suggests that seed endophyte FXZ2 can increase Zn/Cd tolerance of host plant by altering Zn/Cd speciation in rhizospheric soils, as well as exogenous production of phytohormones to promote growth, lowering oxidative damage while enhancing antioxidant properties. For Zn/Cd accumulation, it has opposite effects: Zn uptake in E+ plants was significantly (p<0.05) decreased, while Cd accumulation in E+ plants was significantly (p<0.05) increased. Thus, FXZ2 has excellent application prospects in Cd phytoextraction and decreasing Zn toxicity in agriculturally important crops.